MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DENGAN MEDIA KARTU DOMINO PADA PEMBELAJARAN IPA KELAS IV SEKOLAH DASAR - Aminatu Zuhro (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to improve student learning outcomes with domino card media in class IV Elementary School Science learning. And to find out the learning outcomes of students using domino cards in learning science in grade IV elementary schools. The method in this study uses quantitative research methods by conducting tests of student learning outcomes. The subjects of this study were students of grade IV UPT SDN 107 Gresik, which consisted of 8 students. Based on the results of data analysis of student learning outcomes, it was found that improving student learning outcomes with domino card media in science learning class IV elementary schools, namely domino card media that individual student completeness reached 7 students out of 8 students and classical student completeness reached 87.5%.